Epidemiology and veterinary public policy - Zepeda Sein, Cristóbal Andrés, author; Salman, Mo, advisor (Colorado State University. Libraries, 2008)
Official Veterinary Services are increasingly required to base veterinary public policy decisions on scientific grounds, epidemiology and risk analysis play an important role in shaping these decisions. A formal, in-depth analysis of the multiple interactions between epidemiology, risk analysis and veterinary public policy was conducted to enable decision-makers to direct resources more efficiently and facilitate compliance with international agreements, in particular the Agreement on the Application of Sanitary and Phytosanitary Measures (SPS) of the World Trade Organization. The SPS Agreement recognizes the World Organization for Animal Health (OIE) as the international organization responsible for developing animal health standards. The OIE's Terrestrial Animal Health Code contains scientifically based recommendations for international trade in animals and animal products. However, to date, these recommendations have not been assessed from a risk-based perspective. The study is divided in two major sections: (1) the role of epidemiology in veterinary public policy and (2) the application of risk-based approaches to the assessment of international animal health standards. The first section addresses the international framework, risk analysis and its use worldwide, and the development of international standards. The second section focuses on quantitative risk assessment approaches for the international movement of animals and products, as well as the application of compartmentalization to aquaculture production systems emphasizing the use of a HACCP approach to biosecurity.
Keywords: animal health standards; sanitary measures; veterinary public policy; agronomy